Prevalence of hand pain among dentists present during the 31st Filipino-Chinese dental Foundation Inc. 3rd quarter seminar - Diaz, Nestlie Mae M.
Hand pain is a musculoskeletal disorder which is an occupational hazard and a common complaint in the dental profession, affecting 38% of American dentists. Locally, there has been a study about the prevalence of CTS among dentists in Manila. However, there has been no local research that dealt with the prevalence of both diagnosed and undiagnosed hand pain related to dental work. This study aims to describe the prevalence of hand pain among dentists who are members of the Filipino-Chinese Dental Foundation Inc. and were present during the FCDFI 3rd seminar. Methods: Randomly selected dentists were given a set of forms which include; informed consent, screening, and survey questionnaire. Screening questionnaires were used to determine valid participants. The survey questions were mostly closed type questions and checklists. Hand pain was related to different variables (i.e. profile of the dentists, procedures performed, duration, etc.). Results: 94.9% of the respondents who met the inclusion criteria, and with varying age levels and years of practice reported to have experienced hand pain. 61% of the respondents describe pain to be mild and tolerable and most of the respondents claimed that it had no effect on their dental practice (69.5%) while some needed to reduce work hours (16.9%). Although majority agreed that their hand pain is related of the dental procedures that they do (61%). most of them did not seek medical attention and have not undergone any therapy for their hand pain. Conclusion: There is a high prevalence of hand pain among members of FCDFI who were present at their 3rd quarter seminar. Although most of them claimed that pain is mild in nature, it could possibly worsen and develop to serious pathologies if not given proper attention. Therefore, awareness regarding hand pain is important, and consultation with a physician and practicing proper and ergonomic postures may be advised.